Dimethyl fumarate modulates the regulatory T cell response in the mesenteric lymph nodes of mice with experimental autoimmune encephalomyelitis - Lima, Amanda D. R.; Ferrari, Breno B.; Pradella, Fernando; Carvalho, Rodrigo M.; Rivero, Sandra L. S.; Quintiliano, Raphael P. S.; Souza, Matheus A.; Brunetti, Natália S.; Marques, Ana M.; Santos, Irene P.; Farias, Alessandro S.; Oliveira, Elaine C.; et al. (Frontiers in Immunology, 2024)
Dimethyl fumarate (DMF, Tecfidera) is an oral drug utilized to treat relapsing-remitting multiple sclerosis (MS). DMF treatment reduces disease activity in MS. Gastrointestinal discomfort is a common adverse effect of the treatment with DMF. This study aimed to investigate the effect of DMF administration in the gut draining lymph nodes cells of C57BL6/J female mice with experimental autoimmune encephalomyelitis (EAE), an animal model of MS. We have demonstrated that the treatment with DMF (7.5 mg/kg) significantly reduces the severity of EAE. This reduction of the severity is accompanied by the increase of both proinflammatory and anti-inflammatory mechanisms at the beginning of the treatment. As the treatment progressed, we observed an increasing number of regulatory Foxp3 negative CD4 T cells (Tr1), and anti-inflammatory cytokines such as IL-27, as well as the reduction of PGE2 level in the mesenteric lymph nodes of mice with EAE. We provide evidence that DMF induces a gradual anti-inflammatory response in the gut draining lymph nodes, which might contribute to the reduction of both intestinal discomfort and the inflammatory response of EAE. These findings indicate that the gut is the first microenvironment of action of DMF, which may contribute to its effects of reducing disease severity in MS patients.